Sparse direct solver for large finite element problems based on the minimum degree algorithm. (November 2017) - Pařík, Petr; Plešek, Jiří
Abstract: A sparse direct solver for large problems from solid continuum mechanics based on the minimum degree algorithm is proposed and tested. The solver is designed to take advantage of the properties of the finite element method, particularly the structure of the finite element mesh. For the minimization of the fill-in in the matrix factors a modification of the approximate minimum degree ordering algorithm of Amestoy, Davis and Duff is utilized. The employed sparse matrix storage format and the algorithms for each of the solver phases are also described. The results of numerical tests of the solver on large real-world finite element problems are presented and its performance is compared to a frontal solver and the PARDISO sparse direct solver.